Phytotoxicity of Silver Nanoparticles on Tobacco Plants: Evaluation of Coating Effects on Photosynthetic Performance and Chloroplast Ultrastructure - Petra Peharec Štefanić; Karla Košpić; Daniel Mark Lyons; Lara Jurković; Biljana Balen; Mirta Tkalec (Nanomaterials, 2021)
Silver nanoparticles (AgNPs) are the most exploited nanomaterial in agriculture and food production, and their release into the environment raises concern about their impact on plants. Since AgNPs are prone to biotransformation, various surface coatings are used to enhance their stability, which may modulate AgNP-imposed toxic effects. In this study, the impact of AgNPs stabilized with different coatings (citrate, polyvinylpyrrolidone (PVP), and cetyltrimethylammonium bromide (CTAB)) and AgNO3 on photosynthesis of tobacco plants as well as AgNP stability in exposure medium have been investigated. Obtained results revealed that AgNP-citrate induced the least effects on chlorophyll a fluorescence parameters and pigment content, which could be ascribed to their fast agglomeration in the exposure medium and consequently weak uptake. The impact of AgNP-PVP and AgNP-CTAB was more severe, inducing a deterioration of photosynthetic activity along with reduced pigment content and alterations in chloroplast ultrastructure, which could be correlated to their higher stability, elevated Ag accumulation, and surface charge. In conclusion, intrinsic properties of AgNP coatings affect their stability and bioavailability in the biological medium, thereby indirectly contributing changes in the photosynthetic apparatus. Moreover, AgNP treatments exhibited more severe inhibitory effects compared to AgNO3, which indicates that the impact on photosynthesis is dependent on the form of Ag.